Estressores e variances de bem-estar em pessoas idosas hospitalizadas: teoria de médio alcance de enfermagem - Benetti, Eliane Raquel Rieth (2019)
This study deals with the stressors experienced by hospitalized elderly people and their theoretical relationships with the Neuman’s Systems Model. It is a qualitative research, anchored in the methodological proposal of Convergent Care Research, followed by the steps related to conception, instrumentation, scrutiny and analysis, which supported the development of a Medium-Range Nursing Theory. Research project with ethical appraisal, Opinion nº 1.771.984. The overall goal was to develop a Medium-Range Nursing Theory on stressors and well-being variances in hospitalized elderly people, based on the theoretical synthesis of empirical data and the derivation of concepts from the Neuman’s Systems Model. The study was held at the University Hospital of Santa Maria, with the participation of 30 elderly people hospitalized in medical and surgical clinics and 16 nurses. Participant observation and conversation interview, carried out with hospitalized elderly people, enabled their characterization regarding the physiological, psychological, sociocultural, developmental and spiritual dimensions and the design of intrapersonal, interpersonal and extrapersonal stressors experienced by them during the period of hospitalization. From the stressors, we identified seven nursing diagnoses, for which nursing results, interventions and activities were proposed, validated with 16 nurses, through convergence group meetings. These meetings allowed us to have the opportunity to validate nursing interventions and activities, thereby enabling instrumentalization, reflections on appropriation and the construction of new skills that converges towards changes in care practice. The steps related to data production were characterized by movements of approximation, distancing and convergence between research and care practice. Through data analysis (apprehension, synthesis, theorization and transfer), we established theoretical relationships between stressors and well-being variances in hospitalized elderly people and concepts of the Neuman’s Systems Model, where a Nursing Process was proposed. We have defended the constructed thesis that hospitalization is permeated by stressors, which cause instability in the physiological, psychological, sociocultural, developmental and spiritual dimensions and, consequently, well-being variances in the elderly patients. In these situations, the Rieth-Benetti’s Medium-Range Theory on stressors and well-being variances in hospitalized elderly people directs the nursing process in order to reduce or avoid stressors and contribute to coping and/or adapting to them, thereby maintaining or promoting the well-being of the hospitalized elderly person. It is an abstract enough theory to be applicable to all hospitalized elderly people in different clinical, social, cultural, political and economic contexts. Moreover, it can guide nurses and researchers to apply their concepts in practice, as they are clearly defined and the relationships are explicit in the theoretical structure. Theory can be a useful tool in healthcare practice because it aims to contribute to knowledge, critical thinking and decision making in nursing care for hospitalized elderly people. Due to its originality, this study portrays important constructions for scientific knowledge in the nursing area, given its potential for innovation and its impact on practice, thereby highlighting the potential of qualitative research that converge with the development of nursing theories.